Pengaruh Kadar Gula Darah terhadap Kejadian Reinfark dan Kematian pada Penderita Sindroma Koroner Akut - Jamaludin Jamaludin; Zaenab Djafar (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2015)
Recent decades data relates between admission hyperglycemia and mortality that increase among acute coronary syndrome(ACS) patients. Aim  of study is to assess relationship between hyperglycemia and Cardiac Event, i.e. death, reinfarction among ACS patients. This is a prospective cohort study, which was held on March to April 2014 among 83 ACS patients in CVCU Wahodin Sudorohusodo Hospital. Patients was grouped into two groups, hyperglycemic ACS group and normoglycemic one. Reinfarction and death events at each group was observed within first 30 days after infarction. In this study, it found death and reinfarction events were higher in hyperglycemic group than in normoglycemic group (22 vs 4, RR = 3.7, p=0.026 for death event, and 14 vs 1, RR =8.7, p=0.03 for reinfarction). Conclusion of this study was hyperglycemia is related to reinfartion and death events among ACS patients.Keywords: Acute Coronary Syndrome, Hyperglycemia, Reinfarction, Death